BUDIDAYA MAGGOT BSF (BLACK SOLDIER FLY) SEBAGAI PAKAN ALTERNATIF IKAN LELE (CLARIAS BATRACUS) DI DESA CANDIPARI, SIDOARJO PADA PROGRAM HOLISTIK PEMBINAAN DAN PEMBERDAYAAN DESA (PHP2D) - Ani Masrufah; Khilyatul Afkar; Ahmad Sholahuddin Fawaid; Danul Wildan Alvarizi; Layyinatul Khoiriyah; Miftahul Khoiriyah; Muchammad Abdulloh Kafi; Reta Slakhul Faradilla; Revidal Amsah; Natasya Nur Hidayah; Aulianitha Salsabella; Dinda Ayu Romadhotin Nazwa; Sindi Nur Fadila; Urifatus Eka Kurnia Sari; Fathandy Isragama Naim; Siti Nur Riyana Itsnaini; Muhammad Nadhif Ramadhan (Journal of Science and Social Development, 2020)
The average Indonesian people throw food waste around 300 Kg every year. The large amount of food waste is a problem that must be resolved immediately. Utilizing organic waste as a feed medium for BSF (Black Soldier Fly) maggots is one way of processing and utilizing organic waste. With the help of EM-4 in the fermentation process which creates a distinctive aroma to attract the attention of BSF flies so that they hatch the eggs in the reactor provided. BSF maggot is used as an alternative feed for catfish. In addition, the BSF maggot helps the degradation process of organic waste. Thus, the BSF maggot cultivation training was carried out in the Holistic Development and Village Empowerment Program by utilizing organic waste as a feed medium in Candipari Village. The method of implementation is carried out by lecturing/ socializing and training. High community enthusiasm and increased community knowledge up to 100% in cultivating BSF maggots are benchmarks for the success of this training. Thus, the people of Candipari Village have the potential to become a guided village in BSF maggot cultivation.